Smile makeover with direct composite veneers: A two-year follow-up report - Bora Korkut (Tabriz University of Medical Sciences, 2018)
Direct composite veneers have gained an important role in dental clinical applications following recently developed materials and techniques in adhesive and restorative dentistry. Direct application on prepared tooth surfaces or even without any preparation, with an adhesive agent and a composite resin material in a single visit is the main procedure as well as the advantage of these restorations. The main aim of this direct procedure is to create minimally invasive and long-lasting restorations. As the dental materials and techniques develop, the clinicians also have the chance to mimic the natural dental tissues to create very natural-looking restorations in a single appointment. However, like all the other dental procedures, direct composite veneers have some indications and contraindications. These musts have to be understood very well by the clinician before treatment planning. However, this way direct composite veneers would no longer be named 'day savior fillings' and would be called minimally invasive, functional and long-lasting 'direct aesthetic restorations' that perfectly emulate the natural dental tissues. This article discusses the necessities of direct composite veneers for the ultimate success and illustrates how to perform minimally invasive, long-lasting, functional and natural-looking smile makeovers with these restorations in a single visit.